KOMPOSISI DAN KANDUNGAN PIGMEN UTAMA TUMBUHAN TALIPUTRI Cuscuta australis R.Br. DAN Cassytha filiformis L. - Heriyanto, Heriyanto; Leenawaty, Leenawaty (Makara Journal of Science, 2006)
The Composition and The Content of The Main Pigments on Dodders Plant Cuscuta australis R.Br. and Cassytha filiformis L. Research on dodders plant Cuscuta australis R.Br. and Cassytha filiformis L was done to analyze their pigment composition and content. The pigment composition was analyzed by the use of thin layer chromatography (TLC) method based on spot color and retardation factor. The water content was measured according to Sudarmadji et. al. The chlorophylls and carotenoid contents were calculated by Porra et. al. and Gross equation, respectively. Result showed that Cuscuta australis R.Br. (green yellowish and orange) and Cassytha filiformis L. (green and brown reddish) had similar pigment composition consist of carotene, pheophytin a, chlorophyll a, chlorophyll b and xanthophyll. The average of the chlorophyll content from the highest to the lowest one was Cassytha filiformis L. green followed by Cuscuta australis R.Br. green yellowish and orange, while the total chlorophyll of Cassytha filiformis L. brown reddish was relatively similar with other dodders plant. The average of the carotenoid content from the highest to the lowest was Cuscuta australis R.Br. orange followed by Cuscuta australis R.Br. green yellowish. The pigment content of Cassytha filiformis L. was relatively similar to Cassytha filiformis L. brown reddish.